A Complex Nutrient Exchange Between a Gall-Forming Aphid and Its Plant Host - Chen, Xiaoming; Yang, Zixiang; Chen, Hang; Qi, Qian; Liu, Juan; Wang, Chao; Shao, Shuxia; Lu, Qin; Li, Yang; Wu, Haixia; King-Jones, Kirst; Chen, Ming-Shun (Frontiers in Plant Science, 2020)
It has been a long-standing question as to whether the interaction between gall-forming insects and their host plants is merely parasitic or whether it may also benefit the host. On its host Rhus chinensis, the aphid Schlechtendalia chinensis induces the formation of closed galls, referred to as horned galls. Typically, mature aphid populations comprise thousands of individuals, which is sufficient to cause the accumulation of high CO2 levels in galls (on average 8-fold higher and up to 16 times than atmospheric levels). Large aphid populations also excrete significant amounts of honeydew, a waste product high in sugars. Based on 13C isotope tracing and genomic analyses, we showed that aphid-derived carbon found in CO2 and honeydew was recycled in gall tissues via photosynthesis and glycometabolism. These results indicated that the aphid-gall system evolved in a manner that allowed nutrient recycling, where the gall provides nutrients to the growing aphid population, and in turn, aphid-derived carbon metabolites provide a resource for the growth of the gall. The metabolic efficiency of this self-circulating system indicates that the input needed from the host plant to maintain aphid population growth less than previously thought and possibly minimal. Aside from the recycling of nutrients, we also found that gall metabolites were transported to other parts of the host plant and is particularly beneficial for leaves growing adjacent to the gall. Taken together, galls in the S. chinensis–Rhus chinensis system are highly specialized structures that serve as a metabolic and nutrient exchange hub that benefits both the aphid and its host plant. As such, host plants provide both shelter and nutrients to protect and sustain aphid populations, and in return, aphid-derived metabolites are channeled back to the host plant and thus provide a certain degree of “metabolic compensation” for their caloric and structural needs.